2022
DOI: 10.3390/biom12040509
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Dysfunction in the Pathogenesis of Abdominal Aortic Aneurysm

Abstract: Abdominal aortic aneurysm (AAA), defined as a focal dilation of the abdominal aorta beyond 50% of its normal diameter, is a common and potentially life-threatening vascular disease. The molecular and cellular mechanisms underlying AAA pathogenesis remain unclear. Healthy endothelial cells (ECs) play a critical role in maintaining vascular homeostasis by regulating vascular tone and maintaining an anti-inflammatory, anti-thrombotic local environment. Increasing evidence indicates that endothelial dysfunction is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 106 publications
0
27
0
2
Order By: Relevance
“…In vivo studies by Xie et al ( 32 ) showed that ECs subjected to LSS and disturbed flow undergo increased apoptosis through increased monocyte adhesion and inflammatory responses. While HSS is physiologically observed in the normal abdominal aorta, the laminar flow pattern is switched to LSS patterns exerting additional stress on the endothelium once the aortic tissue is deformed into a bulged structure, introducing new curvatures within the AAA sac ( 33 ). Observations in patients with aneurysms have demonstrated that LSS magnitude is co-incident with rupture sites ( 2 4 , 12 , 34 ), further emphasizing the association between LSS and the severity of AAA.…”
Section: Endothelial and Smooth Muscle Cell Mechanosensors In Aaamentioning
confidence: 99%
“…In vivo studies by Xie et al ( 32 ) showed that ECs subjected to LSS and disturbed flow undergo increased apoptosis through increased monocyte adhesion and inflammatory responses. While HSS is physiologically observed in the normal abdominal aorta, the laminar flow pattern is switched to LSS patterns exerting additional stress on the endothelium once the aortic tissue is deformed into a bulged structure, introducing new curvatures within the AAA sac ( 33 ). Observations in patients with aneurysms have demonstrated that LSS magnitude is co-incident with rupture sites ( 2 4 , 12 , 34 ), further emphasizing the association between LSS and the severity of AAA.…”
Section: Endothelial and Smooth Muscle Cell Mechanosensors In Aaamentioning
confidence: 99%
“…In this last cohort, it has also been shown that tea consumption, rich in catechins, up to ≥2 servings per day, was associated with a lower risk of both non-ruptured and ruptured AAA [ 16 ]. From a mechanistic point of view, diet polyphenols may potentially interfere through their antioxidant properties with many factors involved in AAA development by: reducing inflammation [ 17 ]; restoring endothelial function, [ 18 ] which is known to be altered in AAA [ 19 ]; decreasing DNA global methylation [ 20 , 21 ]; and protecting against telomere attrition [ 22 , 23 ].…”
Section: Novel Therapeutic Options In Aaamentioning
confidence: 99%
“…Various inflammatory cell types in AAA, such as macrophages, CD4 + T cells, and B cells, had great importance in the pathological aortic wall through phenotypic regulation ( 7 ). In addition, continuous crosstalk between various cells also affected the occurrence and development of AAA ( 8 , 9 ). Therefore, the study of cell heterogeneity in the development of AAA may be a breakthrough to further understand its pathogenesis and develop targeted drugs.…”
Section: Introductionmentioning
confidence: 99%